2022
DOI: 10.1186/s12891-022-05241-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prestyloid recess morphology and ulnar-sided contrast leakage in CT arthrography of the wrist

Abstract: Background In wrist arthrograms, aberrant contrast material is frequently seen extending into the soft tissue adjacent to the ulnar styloid process. Since the prestyloid recess can mimic contrast leakage in CT arthrography, this study aims to provide a detailed analysis of its morphologic variability, while investigating whether actual ulnar-sided leakage is associated with injuries of the triangular fibrocartilage complex (TFCC). Methods Eighty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A systematic review of cadaver studies by Koeyvoets et al, showed that transosseous tunnel repair yielded the highest stability for DRUJ and the strongest TFCC repair in comparison to the suture anchor repair and peripheral capsular repair [18]. Gietzen studied the morphology of the ulna fovea using wrist computed tomography arthrography and found that the mean length and anterior-posterior diameter were 6.89 ± 2.36 and 5.05 ± 1.97 mm, respectively [19]. They found that v-RUL and d-RUL possess wide and distinct individual insertion areas.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of cadaver studies by Koeyvoets et al, showed that transosseous tunnel repair yielded the highest stability for DRUJ and the strongest TFCC repair in comparison to the suture anchor repair and peripheral capsular repair [18]. Gietzen studied the morphology of the ulna fovea using wrist computed tomography arthrography and found that the mean length and anterior-posterior diameter were 6.89 ± 2.36 and 5.05 ± 1.97 mm, respectively [19]. They found that v-RUL and d-RUL possess wide and distinct individual insertion areas.…”
Section: Discussionmentioning
confidence: 99%
“…More frequent are ulnodorsal capsular lesions at the triquetral insertion, referred to as ‘Nishikawa injury’ if acute (Nishikawa et al., 2002), or as Triquetral Impingement Ligament Tear (TILT) syndrome if chronic and with interposed synovial tissue (Watson and Weinzweig, 1999). In MR and CT arthrography, these injuries are best visualized in the sagittal plane (Gietzen et al., 2022; Theumann et al., 2011). Tears of the ulnocarpal meniscus with fracture of the tip of the ulnar styloid process usually do not cause instability (Type P1#).…”
Section: Class P Lesionsmentioning
confidence: 99%